The Caregiving Experiences of Fathers and Mothers of Children With Rare Diseases in Italy: Challenges and Social Support Perceptions - Cardinali, Paola; Migliorini, Laura; Rania, Nadia (Frontiers in Psychology, 2019)
Family caregiving is a growing phenomenon with the increased prevalence of chronic illness and shorter hospitalizations. Rare diseases pose significant challenges not only to patients living with these kinds of pathologies but also to those who care for these patients. The caregiving role has specific characteristics. The present work aims to increase knowledge of the challenges that are common or specific to fathers and mothers of children diagnosed with a rare disease. Moreover, the paper analyses the kinds of social support they experience according to gender. A descriptive study was conducted using grounded theory methodology. A semi-structured interview with open-ended questions was conducted with 15 parents of children with a rare disease. The interview was organized into three main areas: personal experiences in caring for a child with a rare disease, family changes and perceived social support. The transcriptions were analyzed using NVivo 11 software. From data analysis, themes emerged regarding the challenges shared by fathers and mothers, but some aspects also emerged that were gender-specific. The analyses of differences between mothers’ and fathers’ narratives showed that there is a specific experience of the impact that caregiving has on parents’ relationships with their jobs and on their worries. Self-help group is the main source of social support for all respondents. We discuss these findings in relation to possible appropriate specific interventions and support for family caregiving.